Innovation of Substitute Material to Conservation Effort of Eusideroxylon Zwageri on Wooden Bridge Maintenance Project - Minarni, Ita; Wardhana, Henry; Asyari, Mufidah; Mursadin, Aqli (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Infrastructure in the form of bridges is very important for Buntok Regency in Central Kalimantan where the area is swampy or lowland area. Total wood bridge construction is 45% from total 163 bridge in this area that most of them are not proper condition considering some wood materials need to be replaced. The innovation has been created to find the effective way how to maintenance the wooden bridge that has been idle for long time due to broken material on superstructure of the bridge. The floor of bridge that constructed with previous materials of ulin wooden bridge replaced by composite materials with floordeck concrete combination. The implementation of Tampa Bridge maintenance innovation showed better performance in terms of safety, comfortable and smoothness of bridge users from community around. In terms of budget aspect, the maintenance is cumulatively more efficient than if carrying out floor changes every year considering no longer possible to find ulin wood anymore. On technical point of view, with reinforced concrete can be applied to wooden bridges selectively only on ulin wooden bridges whose substructure is still intact and only minor damage to the spoorband and floor occurs. Bridge maintenance procedures need to be create to keep better maintenance for longer life time of the existing bridge that can be applied for another wooden bridge for maintenance.